Review on Fake Iris Detection Method using Image Quality Assessment (International Journal of Current Engineering and Technology, 2015)
A biometric system is a computer system which is used to identify the person on their behavioral and physiological characteristic for example fingerprint, face, iris, key-stroke, signature, voice, etc. A typical biometric system consists of sensing, feature extraction, and matching modules. But now a day’s these systems are attacked by using fake biometrics. To ensure the actual presence of a real legitimate trait in contrast to a fake self-manufactured synthetic or reconstructed sample is a significant problem in biometric authentication, which requires the development of new and efficient protection measures. The proposed system presents a novel software-based fake detection method that can be used in multiple biometric systems to detect different types of fraudulent access attempts. The objective of the proposed system is to enhance the security of biometric recognition frameworks, by adding assessment in a fast, user-friendly, and non-intrusive manner, through the use of image quality assessment.
Keywords: Attacks; Biometrics; Countermeasures; Image Quality Assessment; Security